Algebraic and Numeric Biology 4th International Conference, ANB 2010, Hagenberg, Austria, July 31- August 2, 2010, Revised Selected Papers - Horimoto, Katsuhisa; Nakatsui, Masahiko; Popov, Nikolaj; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 4th International Conference on Algebraic Biology, ANB 2010, held at the Castle of Hagenberg, Austria in July/August 2010. The conference is a follow up of the AB Conference. The 10 papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on mathematical modeling, system analysis and design, genomics, molecular structure analysis, automata theory, artificial intelligence, sequence analysis, automated reasoning, formal language and hybrid symbolic numerical methods.
Keywords: Computer science; Software engineering; Logic design; Algebra -- Data processing; Bioinformatics; Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Symbolic and Algebraic Manipulation; Computational Biology/Bioinformatics.; Software Engineering; Programming Languages, Compilers, Interpreters